2010
DOI: 10.1111/j.1365-2214.2009.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Why immunization coverage fails to catch up in India? A community‐based analysis

Abstract: Universal immunization can be achieved by providing services at community level and information about the available services and their benefits to the community. There is a considerable, unexplained variation in the immunization coverage between different communities, even in the most complex model used in this study, which could explain the entire heterogeneity of immunization coverage among Indian states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This study showed that, irrespective of the number of ANC visits by the mother, those who had ANC attendance had higher likelihood of having their children fully immunised than mothers who had no ANC attendance. This is consistent with studies in Senegal,35 Bangladesh,36 Indonesia,37 India,38 and Zimbabwe,39 which showed that ANC attendance of the mother was significantly associated with increased likelihood of a child to be fully immunised. In contrast, Lakew et al 40 showed that ANC attendance was not associated with fully immunised children in Ethiopia 40.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that, irrespective of the number of ANC visits by the mother, those who had ANC attendance had higher likelihood of having their children fully immunised than mothers who had no ANC attendance. This is consistent with studies in Senegal,35 Bangladesh,36 Indonesia,37 India,38 and Zimbabwe,39 which showed that ANC attendance of the mother was significantly associated with increased likelihood of a child to be fully immunised. In contrast, Lakew et al 40 showed that ANC attendance was not associated with fully immunised children in Ethiopia 40.…”
Section: Discussionsupporting
confidence: 91%
“…The purpose of this approach is to control the correlation between individual characteristics in a particular community. The community error term uj in the model gives an indication of the variation after controlling for the individual characteristics [23].…”
Section: Methodology Multilevel Analysismentioning
confidence: 99%
“…Sahu et al (2010) also saw that infants living in communities with all weather roads, public sector health facilities had higher complete vaccination coverage compared to their counterparts. (7) …”
Section: Discussionmentioning
confidence: 99%